2001
DOI: 10.1177/0734242x0101900412
|View full text |Cite
|
Sign up to set email alerts
|

A solid waste audit and directions for waste reduction at the University of British Columbia, Canada

Abstract: A novel design for a solid waste audit was developed and applied to the University of British Columbia, Canada, in 1998. This audit was designed to determine the characteristics of the residual solid waste generated by the campus and provide directions for waste reduction. The methodology was constructed to address complications in solid waste sampling, including spatial and temporal variation in waste, extrapolation from the study area, and study validation. Accounting for spatial effects decreased the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 9 publications
1
37
0
2
Order By: Relevance
“…The institution accommodates the bulk of younger population and must be given proper training on SWM. Further, schools with better SWM practice showed positive response by providing SW recycling options (Smyth et al, 2010;Mbuligwe, 2002;Mason et al, 2003;Malakahmad et al, 2010;Kelly et al, 2006;Felder et al, 2001;De Vega et al, 2003;. Consequently, schools can implement a structure to mitigate SWM issues.…”
Section: Introductionmentioning
confidence: 99%
“…The institution accommodates the bulk of younger population and must be given proper training on SWM. Further, schools with better SWM practice showed positive response by providing SW recycling options (Smyth et al, 2010;Mbuligwe, 2002;Mason et al, 2003;Malakahmad et al, 2010;Kelly et al, 2006;Felder et al, 2001;De Vega et al, 2003;. Consequently, schools can implement a structure to mitigate SWM issues.…”
Section: Introductionmentioning
confidence: 99%
“…Planning a waste characterization study requires many considerations, ranging from the selection of sorting categories, to techniques for capturing the spatial and temporal variation of the waste (Felder et al 2001). The challenge is to collect waste generation and composition data which is representative of the entire campus, with the intention that plans for waste reduction and diversion will be based on the reality of the existing campus waste stream.…”
Section: Campus Waste Characterization Studiesmentioning
confidence: 99%
“…Also, few papers have been published that report the results of campus waste characterization studies (Felder et al 2001;Armijo de Vega et al 2008) creating further challenges for accessing data. Of these papers only a single study can be found for a Canadian IHE (Felder et al 2001).…”
Section: Campus Waste Characterization Studiesmentioning
confidence: 99%
See 2 more Smart Citations